Facilitating Improvement of Design for Safety and Operations of a Seaweed Harvester: A Hybrid Traditional Safety Method - Nwaoha, Thaddeus Chidiebere; Emovon, Ikuobase (International Journal of Integrated Engineering, 2018)
Sea harvester is a vital marine vessel needed in sea safety and cleanliness. Reliability and safety of the operations of the vessel need to be ensured via identification of hazards/failures that tends to affect the system and prevent them from occurring and also mitigate their consequences. In this research, a traditional hybrid methodology is employed in ensuring the reliability and safety of a sea harvester. The methodology is a logical combination of preliminary hazard analysis (PHA), risk matrix approach (RMA) and event tree analysis (ETA). Fire, flood, machinery failure and capsize that pose to affect optimal operations of a sea harvester are identified using a PHA method. RMA is incorporated in application of the PHA method to estimate the risks associated with them. Due the fact that risks associated with fire, flood, machinery failure and capsize are classified as very high, identifying preventing measures becomes necessary. Furthermore, systems which by means of their operability and non-operability can mitigate fire, flood, machinery failure, capsize and grounding consequences are captured using an ETA method. Therefore, the traditional hybrid methodology developed is successfully applied in design for safety, construction and operation of a sea harvester